2007
DOI: 10.1590/s1414-81452007000400017
|View full text |Cite
|
Sign up to set email alerts
|

Predisposição ao uso e abuso de álcool entre estudantes de graduação em enfermagem da UFRN

Abstract: Estudo de natureza exploratória descritiva com abordagem quantitativa, avaliou a predisposição para o uso e abuso do álcool na Graduação em Enfermagem/UFRN. A amostra foi composta por 42 alunos regularmente matriculados, sendo 76% do gênero feminino. Utilizou-se o questionário CAGE acrescido de itens sobre a síndrome da abstinência alcoólica. Metade (50%) faz uso de álcool, com idade entre 21 e 22 anos (41%). O maior consumo está no quinto período (38%), seguido do terceiro (19%). Dentre os pesquisados, 34% se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 5 publications
1
7
0
11
Order By: Relevance
“…15 As to gender, there were no difference the risk levels between men and women corroborating with others studies. [3][4][6][7]15 The same was verified with students from others areas. 16 Researches indicate there is a female trend increasingly to consume alcoholic beverages.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…15 As to gender, there were no difference the risk levels between men and women corroborating with others studies. [3][4][6][7]15 The same was verified with students from others areas. 16 Researches indicate there is a female trend increasingly to consume alcoholic beverages.…”
Section: Discussionmentioning
confidence: 57%
“…4,6 Research conduced with nursing students at Brazilian Northeast found a strong tendency for consumption problematic use when was evaluated the difference between sex , especially for female. 7 These results do not differ from investigations conducted with nursing students from south of the country which 90% used alcoholic beverages and these 14% were on alcohol intoxication level, five or more doses any occasion. 13 Both Brazilian region south and mid-western has identified nursing students with problematic drinking, especially young women.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations